JUMPA Vol.2 No.1 Feb 2015 PENGARUH FAKTOR BUDAYA, SOSIAL, DAN KARAKTERISTIK PRIBADI TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE MEREK BLACKBERRY PADA MAHASISWA S1 FAKULTAS EKONOMI & BISNIS UNIVERSITAS MERCUBUANA JAKARTA: PENGARUH FAKTOR BUDAYA, SOSIAL, DAN KARAKTERISTIK PRIBADI TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE MEREK BLACKBERRY PADA MAHASISWA S1 FAKULTAS EKONOMI & BISNIS UNIVERSITAS MERCUBUANA JAKARTA - Christina Catur Widayati Fakultas Ekonomi dan Bisnis Universitas Mercu Buana Jakarta; Ryani Dhyan Parashakti Fakultas Ekonomi dan Bisnis Universitas Mercu Buana Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
The purpose of this study was to examine or analyze the influence of cultural, social, and personal characteristics of the product purchase decision Blackberry smartphone brand in S1 Faculty of Economics and Business UMB. The method used in this research is the method of sampling is not random, and the sample selection technique used in this study was not a random sample selection technique convenient. This study uses primary data is to spread the questionnaire on student / student of the Faculty of Economics and Business UMB generation 2012. The results of the data analysis and hypothesis testing, it can be concluded that there is a positive influence and variables: the cultural, social, and personal characteristics either partially or simultaneous to the Blackberry brand smartphone purchase decision. Test results F = 321.204, and (R2) = 95.1% of the three independent variables were examined turns cultural variables is the most dominant variable in influencing purchase decisions smartphone Blackberry brand.